Integrated block copolymer prodrug nanoparticles for combination of tumor oxidative stress amplification and ROS-responsive drug release. (March 2019) - Yin, Wei; Ke, Wendong; Chen, Weijian; Xi, Longchang; Zhou, Qinghao; Mukerabigwi, Jean Felix; Ge, Zhishen
Abstract: In tumor tissues, reactive oxygen species (ROS) level is significantly higher than that in normal tissues, which has been frequently explored as the specific stimulus to trigger drug release. However, the low intrinsic ROS concentration and heterogeneous distribution in tumor tissues hinder the applications as the stimulus for drug delivery. Herein, we developed integrated nanoparticles to remold tumor microenvironment via specific amplification of the tumor oxidative stress and simultaneously realize ROS-responsive drug release. The amphiphilic block copolymer prodrugs composed of poly(ethylene glycol) and polymerized methacrylate monomer containing thioketal-linked camptothecin (CPT) were synthesized and self-assembled to form core-shell micelles for encapsulation of β -lapachone (Lapa@NPs). After tumor accumulation and internalization into tumor cells post systemic administration of Lapa@NPs, Lapa can selectively induce remarkable ROS level increase via the catalysis of NAD(P)H: quinone oxidoreductase-1 (NQO1) enzyme overexpressed in cancer cells. Subsequently, enhanced ROS concentration would trigger the cleavage of thioketal linkers to release drug. The released CPT together with high ROS level achieved a synergistic therapy to suppress tumor growth. Moreover, Lapa@NPs exhibited superior biosafety due to the tumor-specific activation of the cascade reaction. Accordingly, Lapa@NPs represent a novel polymer prodrug design and drug release strategy via tumor-specific oxidative stress amplification and subsequent ROS-responsive drug release. Graphical abstract: